The Theatre Organised by the Industrial and Handicraft Youth Association in Krakow - Inspired by Father Mieczysław Kuznowicz, a Graduate of the Jesuit School in Chyrów - Małgorzata Puchowska (Jesuit University Ignatianum in Krakow, 2015)
The theatre established by the Industrial and Handicraft Youth Association is a representative of the amateur theatre movement, typical for Krakow during the inter-war period. However, it has one remarkable feature - it was created by young people from very diverse social backgrounds, far from the gymnasium elite, often illiterate. They were connected by common passion and artistic needs, awakened by the creative educational concept of Father Mieczysław Kuznowicz. The aim of the theatre on Skarbowa Street was to use appropriate dramatic texts to develop religious, national and social feelings among the members of the association, to teach proper communication in the mother tongue and to form the habits of cultural behaviour and solid teamwork. The form of the youth theatre adopted in the association seems to correspond with the concept known from the theatrical stages of Jesuit schools. The author attempts to answer the following question: "To what extent did the experiences of Kuznowicz, a graduate of the Scientific and Educational Department of the Jesuits in Chyrów, influence the shape of the theatrical stage in Krakow?" STRESZCZENIE   Teatr Związku Młodzieży Przemysłowej i Rękodzielniczej w Krakowie - chyrowskie inspiracje księdza Mieczysława Kuznowicza. Scena Związku Młodzieży Przemysłowej i Rękodzielniczej z jednej strony wpisuje się w typowy dla Krakowa okresu 20-lecia międzywojennego ruch teatrów amatorskich, z drugiej posiada cechę niezwykłą - tworzyli ją młodzi ludzie pochodzący z bardzo odmiennych środowisk społecznych, dalekich od elit gimnazjalnych, często analfabeci. Jednoczyły ich wspólne pasje i potrzeby artystyczne, rozbudzane twórczą koncepcją wychowawczą księdza Mieczysława Kuznowicza. Celem działalności teatru przy ulicy Skarbowej stało się rozwijanie wśród członków Związku, za pomocą odpowiedniej literatury dramatycznej, uczuć religijnych, narodowych i społecznych, uczenie poprawnego komunikowania się w języku ojczystym oraz wpajanie nawyków kulturalnego zachowania, a także solidnej, zespołowej pracy. Przyjęta w Związku formuła teatru młodzieżowego zdaje się korespondować z koncepcją znaną z działalności szkolnych scen konwiktów jezuickich. Autorka stara się, w kontekście wychowania przez pracę oraz edukacji przez sztukę, odpowiedzieć na pytanie, w jakiej mierze doświadczenia Kuznowicza, absolwenta Zakładu Naukowo-Wychowawczego w Chyrowie, wpłynęły na kształt tej krakowskiej sceny.